Student ID Validation Monitoring System - Muelan, Aira Mae Failagao; Decomotan, Kyla Marie Garantosa; Lebuna, Jerico Nique (IC-ITECHS, 2024)
The Student ID Validation Monitoring System (SIVMS) is a web-based system aimed to monitor students' ID validation status at Iloilo Science and Technology University Miagao Campus. This system was created to address the challenge faced by the Office of Student Affairs and Services Miagao Campus in ensuring only students with validated ID are in the campus, enhancing safety, and security. By utilizing QR code scanning technology, the system ensures quick and accurate tracking of student validation status. The main objective of the study was to develop a system that manages student profiles, generates unique QR codes for each student, and enables security personnel to monitor student ID validation status. The system also has the ability to generate reports and was evaluated using the ISO 25010 software quality model. Built with HTML, CSS, PHP, and MySQL, the system followed the Iterative Software Development Methodology, ensuring continuous improvements through user feedback. The evaluation results, based on the ISO/IEC 25010 criteria, showed an overall rating of "excellent," with a mean score of 4.52. The system met the standards for functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability. In conclusion, the study successfully achieved its goal of developing the SIVMS, improving campus security, and supporting university policy enforcement.